Effect of a Genetic Counselling Educational Intervention on Nurses' Knowledge and Self-Reported Skills for Breast Cancer Risk Assessment in Ekiti State, Nigeria - Oluwabunmi Adeniji (The Nursing Scope, 2026)
Background: Breast cancer remains one of the leading causes of cancer-related morbidity and mortality among women worldwide, and genetic predisposition is an important contributor to susceptibility. As frontline healthcare professionals, nurses play a critical role in identifying individuals at risk and providing genetic information and referrals. However, deficiencies in nurses' knowledge and skills regarding genetic assessment and counselling continue to limit the effective integration of genomics into routine nursing practice. Aim: This study determined nurses' baseline knowledge of genetic assessment and counselling and evaluated the effect of a genetic counselling educational intervention on their knowledge and self-reported skills for breast cancer risk assessment in Ekiti State, Nigeria. Method: A quasi-experimental pre-test/post-test control-group design was employed among 400 nurses from three tertiary hospitals in Ekiti State, Nigeria. Participants were assigned to intervention (n = 200) and control (n = 200) groups via multistage sampling with simple random allocation. Baseline data were collected using the Genetic and Genomic Nursing Practice Survey (GGNPS). The intervention group received structured education on genetic assessment and counselling; the control group received standard breast cancer education. Post-intervention assessment occurred six weeks later, and data were analysed using independent- and paired-samples t-tests at p < 0.05. Findings: Following the intervention, nurses in the intervention group demonstrated significantly higher knowledge scores than those in the control group (6.07 ± 0.91 vs. 5.72 ± 1.09; t(385.46) = –3.55, p < 0.001). Significant improvements were also observed in participants' self-reported skills in obtaining comprehensive family histories, identifying individuals requiring genetic counselling referral, assessing genetic susceptibility to breast cancer, and communicating the benefits, risks, and limitations of genetic testing. Conclusion: The genetic counselling educational intervention significantly improved nurses' knowledge and self-reported skills in genetic assessment and counselling for breast cancer risk assessment. Strengthening genetics and genomics education among nurses may enhance breast cancer prevention, early detection, and evidence-based patient care. Recommendation: Genetics and genomics education should be integrated into undergraduate nursing curricula, continuing professional development programmes, and institutional in-service training to improve nurses' competence in genetic risk assessment and counselling for breast cancer prevention and early detection. Keywords: Breast cancer; educational intervention; genetic assessment; genetic counselling; knowledge; nurses; self-reported skills.